AN ANALYSIS ON THE INFLUENCE OF PRODUCT INNOVATION, PRODUCT QUALITY, AND PRICE PERCEPTION ON PURCHASE DECISION OF MITSUBISHI FUSO CANTER TRUCKS (A Case Study on Mitsubishi Fuso Canter Truck Owners in Driyorejo District) - Achmad Fathoni Rodli; Rudi Wibowo; Nuning Nurna Dewi (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2022)
The purpose of this research is to determine the influence of product innovation, product quality, and price perception both partially and simultaneously on purchase decision of Mitsubishi Fuso Canter trucks and to figure out the dominant independent variables influencing the dependent variable. This research was conducted in Driyorejo District with the population of all Mitsubishi Fuso Canter truck owners. Since the total number of Mitsubishi Fuso Canter truck owners in Driyorejo District were unknown, the samples were selected using a simple random sampling technique with Lemeshow formula. Thus, 96 research respondents were obtained. The collected data were then processed using a linear multiple regression analysis with hypothesis t and f tests and analysis of determination coefficient (R2) using SPSS 21.0 program. Based on the regression analysis results, a positive value equation of Y = 6.212 + 0.341X1 + 0.313X2 + 0.055X3 + € was obtained. From the research findings, the t-test results showed that product innovation and product quality positively and significantly influenced purchase decision with the dominant variable of product quality. Meanwhile, price perception did not influence purchase decision. The f-test results showed that simultaneously, all independent variables positively and significantly influenced purchase decision proven by the value of f-count (33.575) > that of f-table (2.70). From the analysis results, the determination coefficient (R2) showed the value of 0.523, meaning that simultaneously, product innovation, product quality, and price perception had the contribution of 52.3% on purchase decision, while the remaining 47.7% was the contribution of variables not included in this research.